Sociodemographic, Clinical, and Behavioral Factors Associated With Sexual Transmitted Infection Among HIV-1 Positive Migrants in Portugal: Are There Differences Between Sexes? - Miranda, M (2024)
Introduction: Sexually transmitted infections (STIs) continue to occur at high levels. According to the WHO, each year there are an estimated 374 million new infections with syphilis, gonorrhea, chlamydia, and trichomoniasis. STIs are associated with an increased risk of acquiring HIV infection. Migrants are reportedly highly affected by STIs. Objectives: This study aims to characterize factors associated with STIs in a population of HIV-positive migrants living in Portugal. Methodology: This is a cross-sectional observational study of 265 newly diagnosed HIV-1 positive migrants, who were defined as individuals born outside Portugal. This group of people were part of the BESTHOPE study that was developed in 17 Portuguese hospitals between September 2014 and December 2019, and included information collected through sociodemographic and behavioral questionnaires filled in by the migrant patients, clinical questionnaires filled in by the clinicians and HIV-1 genomic sequences generated through resistance testing (Sanger sequencing). A multivariable statistical analysis was used to analyze the association between sociodemographic characteristics, sexual behaviors, HIV testing and sexual infections. Results: Most HIV-1 positive individuals included in the study were men (66.8%) and aged between 25 and 44 years old (59.9%). Men had a higher proportion of STIs when compared to women (40.4% vs. 14.0%) and the majority of men reported homosexual contacts (52.0%). Most men reported having had two or more occasional sexual partners in the previous year (88.8%) and 50.9% reported always using condoms with occasional partners, while 13.2% never used it. For regular partners, only 29.5% of the women reported using condoms, compared to 47.3% of men. Other risk behaviors for acquiring HIV, such as tattooing and performing invasive medical procedures, were more prevalent in men (38.0% and 46.2%, respectively), when compared to women (30.4% and 45.1% respectively) and 4.7% of men reported having already shared injectable materials, with no data for comparison in the case for women. Additionally, 23.9% of women reported having had a blood transfusion while only 10.3% of men reported having had this medical procedure. Meanwhile, 30.9% of the individuals reported having been diagnosed with some type of STI in the last 12 months. In addition, 43.3% of individuals that answered a question about hepatitis reported to be infected with hepatitis B, while 13.0% reported having hepatitis C infection. According to the multivariable analysis, the only transmission route was significantly associated with reports of previous STI infection: men who have sex with men (MSM) were 70% more likely to have been diagnosed with an STI in the past 12 months compared to the heterosexual route. Conclusion: HIV-1 infected men were more likely to report previous STIs than women. On the other hand, most migrant women had a regular sexual partner and never or only sometimes used condoms. This somewhat discrepant findings suggest that gender inequalities may make women unable to negotiate safe sexual practices, resulting in increased susceptibility to infection. However, since migrant women report less STIs, we cannot exclude that these STIs may remain undiagnosed. The implementation of safer sex awareness campaigns for condom use and screening for STIs in women is crucial. On the other hand, health education campaigns for STI knowledge need to be implemented for both MSM and women and their partners.